Effects of mitomycin C and cyclosporine A on experimentally induced glaucoma filtration surgery in rabbit model - Kilic, S.; Kulualp, K.; Muzoglu, O.; Ozkaraca, M. (Ecole Nationale Veterinaire Toulouse, 2016)
The present study aims at investigating the effect of topical administration of mitomycin C (MMC) used solely and combined with cyclosporine A (MMC+CsA) on inhibition of the granulation tissue proliferation in experimentally induced glaucoma filtration surgery (GFS) in rabbits. A total of 18 New Zealand breed rabbits, control, MMC, and MMC+CsA groups of 6 subjects in each were used in the study. Clinical signs and complications in GFS region were evaluated using ophthalmoscopy, Schirmer tear test and tonometry 7 times at predetermined intervals between days 0-35. The right eyes of all subjects euthanized at the end of the study were harvested and histopathologically evaluated. According to clinical findings, GFS remained patent in all group subjects during the study except two subjects in the control group. Histopathological examination revealed marked cellular activities around GFS of the control group subjects as compared to the MMC and MMC+CsA groups. In this respect, no difference exists between two experimental groups. It has been observed that the intraocular pressure (IOP) value significantly decreased (P<0.005) in all groups on the day 5, which continued until the day 25 in control and MMC groups, and until the day 20 in the MMC+CsA group. The change in tear production rate showed to be more stable in the MMC+CsA than in the control and MMC groups. MMC and MMC+CsA are determined to have inhibited successfully granulation tissue proliferation around GFS and no marked difference was found between them as compared to the control group. It is suggested that in order to observe difference between these two groups, a more prolonged study is required.
Keywords: rabbit; glaucoma filtration surgery; mitomycin C; cyclosporine A